Soviet-Cuban relations after the Caribbean crisis, the collapse of détente and lessons for the future - B. F. Martynov (Ибероамериканские тетради)
The results of the Caribbean crisis in the domestic and foreign literature have rarely been covered from the point of view of the Soviet-Cuban relations that influenced the internationalist policy of Cuba in Africa in the 1970s. The author analyzes: the degree of independence of Cuba’s policy in Africa, the participation of the USSR in it and the fairness of accusations brought by Washington. The results of the analysis show that deploying of Cuban “volunteers” in Angola and then in Ethiopia was not initiated by the USSR, which aimed at maintaining détente in relations with the West. Moreover, new deterioration of relations with Cuba amid escalating Chinese-Soviet tensions, increasing centrifugal tendencies in the “socialist commonwealth” and emergence of “Eurocommunism” threatened to further weaken the “world system of socialism” and erode the ideological foundations of Marxism-Leninism. By analyzing Cuba’s internationalist activity in Africa, the author has been able to draw some conclusions about its implications for the international communist movement and its influence on the balance of power in the world before perestroika policy began in the Soviet Union. The end of détente policy did not allow the USSR to redirect the resources released from the arms race to improving the living conditions of the Soviet people. Cuban revolutionary activity contributed to fragmentation of the formerly united “upfront antiimperialist forces.” The weakening of the ideological foundations of “real socialism” was an additional factor that prompted the Soviet leadership, represented by Mikhail Gorbachev, to begin a policy of perestroika. Cuba’s ‘progress’ in Africa contributed to consolidation of Cuban society around the policy of the Cuban Communist Party, which, in turn, helped it to withstand the difficulties of the “peculiar period of peace” in the early 1990s.